TRADISI PELAKSANAAN RATIB MAKAM DATUK DIRAMBAI DI DESA TELUK NILAP KECAMATAN KUBU BABUSSALAM (STUDI TENTANG SISTEM RELIGI PADA MASYARAKAT MELAYU KUBU) - Maimunah "; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was carried out in Teluk Nilap Village, Kubu Babussalam Subdistrict. The purpose of this study was to determine the implementation of Ratib Tradition in the Tomb of Datuk Rambai in Teluk Nilap Village, Kubu Babussalam Subdistrict. The topic of this research focus is the Belief System in the Community About the Ratib Tradition, the Tomb of Datuk Rambai, Teluk Nilap Village, Kubu Babussalam Subdistrict. The technique of determining samples by purposive sampling and setting the number of samples as many as 5 people. The author uses qualitative descriptive methods and data instruments are observation, interviews and documentation. The study found that the Ratib Tradition of the Tomb of Datuk Dirambai is a hereditary tradition that is still carried out today. This tradition is carried out by key implementers such as leaders, government and community members. Before 1982, this ritual was no longer held every year, but sometimes 10 once a year, sometimes once every 5 years depending on when there is time for plague and reinforcements. But after the 1900s the routine of ratib rambai was routinely performed every year. The ratib rambai tradition was held on the fourth day of Eid al-Fitr, the study found a shift in the implementation time of Ratib Rambai. Previously, Ratib Rambai was held for three consecutive days, but after the 1990s it was only a day in a year. The implementation of the Ratib tradition is carried out in a mobile manner, using motorized boats. In the past people used canoe boats. The community which at the beginning of this ratib began to be carried out from many years ago had believed that it would be able to resist reinforcements. Society is no longer bound by the ratib rambai cultural values as a sacred tradition. But as an effort to maintain culture or identity. This tradition should still be developed without having to get rid of the true meaning of the ratib tradition itself. Keywords: Tradition, Culture, Ratib Dirambai